التسوية الودية للنزاعات الناتجة عن اتفاقيات تفويض المرفق العام في الجزائر -نظرة قانونية- - عوادي, مصطفى; صحراوي, العيد (جامعة الوادي - University of Eloued, 2020)
لقد انتقل المشرع الجزائري من جعل الأساليب العامة لتسيير المرفق العام هي المسيطرة على نشاط هذه الأخيرة، وبدأ يتجه نحو ما ذهبت إليه الكثير من تشريعات العالم وخاصة الفرنسية منها لإشراك الخواص في تحقيق المصلحة العامة بتسيير مرافق حيوية في المجتمع عن طريق تفويضات المرفق العام حسب ما نص عليه المرسوم الرئاسي 15/247 المتعلق بالصفقات العمومية، ونظمه المرسوم التنفيذي 18/199 المتعلق بتفويض المرافق العامة، وتعتبر الشراكة مع القطاع الخاص أهم وسيلة تستعملها الإدارة العامة وخاصة الجماعات المحلية من أجل القيام بالأعباء والمهام المطلوبة، ومن أجل القيام بالعملية التنموية الشاملة، ويعتبر التفويض من أهم أشكال هذه الشراكة بين الادراة العامة والمفوض له، لكن هذه الشراكة قد تشوبها نزاعات تتكفل بها حسب القانون لجان تسوية ودية، لذالك فالهدف من هذا المقال هو التطرق لهذه اللجان ومدى مساهمتها في حل النزاعات لكن النتيجة كانت وجود نقائص كثيرة في هذا الموضوع يجب تداركها من طرف المشرع. The Algerian legislator has moved from making the general methods of managing the public utilities the dominant of the activity of the latter, and has begun to move towards what many of the world’s legislation, especially the French ones, have gone to involve the private sector in achieving the public interest in running vital utilities in society through the mandates of the public utilities as stated in the text It has Presidential Decree 15/247 related to public deals, and was organized by Executive Decree 18/199 related to the delegation of public utilities, The Partnership with the private sector is considered the most important means used by the public administration, especially local groups, to carry out the burdens and tasks required, and in order to carry out the comprehensive development process, and the delegation is considered one of the most important forms of this partnership between the public administration and its delegate, but this partnership may be marred by conflicts that are guaranteed by law amicably settlement committees, so the aim of this article is to address these committees and the extent of their contribution to resolving disputes, but the result was the presence of many shortcomings in this matter that must be rectified by the legislator
AMICABLY SETTLEMENT OF DISPUTES RESULTING FROM PUBLIC AUTHORIZATION AGREEMENTS IN ALGERIA - LEGAL PERSPECTIVE
مقال
Keywords: المرسوم التنفيذي 18/199 ; تفويض المرفق العام ; التسوية الودية ; السلطة المفوضة ; المفوض له ; اللجنة; Executive Decree 18/199 ; Authorizing the public facility ; amicably settlement ; Delegated authority ; The delegate ; The Commission